COVID-19 Infection risk among hemodialysis patients in long-term care facilities (2020)
COVID-19 is killing at horrific rates in long-term care facilities.1 In Massachusetts, 65% of COVID-19 fatalities have been long-term care residents as of July 21, 2020,2 Like their long-term care counterparts, hemodialysis patients are at high-risk for COVID-19, with extensive comorbidity, care in a congregate setting, and frequent interactions with health professionals. The best tool against COVID-19 is physical distancing. Yet this is challenging for hemodialysis patients and long-term care residents, especially for those who are both. Hemodialysis treatments occur in a congregate setting, and many travel to the dialysis facility via public/shared transport or ambulance. Some are non-ambulatory, requiring human assistance for basic activities such as getting dressed. In long-term care, rooms and bathrooms are often shared. For those hemodialysis patients who reside in long-term care, the burden of both settings makes COVID-19 exposure extremely likely. Notably, the first two identified U. S. COVID-19 fatalities were hemodialysis patients, one of whom lived in long-term care.